Budaya Kontemporer dan Dilema Desain Copycat: Analisis Keberlanjutan Industri Sepatu Lokal di Indonesia - Rafi Hafizhni Anggia; Hanindito Prabandaru; Fia Izzah Maylinda; Nora Hafildah (INSTITUT SENI INDONESIA PADANGPANJANG, 2026)
The rapid growth of the local footwear industry in Indonesia faces challenges from dynamic contemporary cultural trends and the widespread phenomenon of copycat design strategies. This study aims to analyze how the influence of popular culture and the adoption of designs similar to global brands impact the business sustainability of local labels. Using a qualitative method with a case study approach, this research explores consumer perceptions and manufacturer strategies. The results indicate that while contemporary culture enhances market relevance, reliance on copycat strategies creates legal risks and long-term brand identity degradation. These findings conclude that the sustainability of local footwear brands heavily depends on transitioning from imitation to original innovation based on unique local cultural values.